Sesqui-Centennial Exposition March - John Philip Sousa::::::::: (Sam Fox Publishing Co.)
Piano score, 6 p. At head of title: To the Honorable The Mayor of Philadelphia, W. Freeland Kendrick, President of the Sesqui-Centennial Exposition. At head of title on cover: Souvenir edition. Publishers advertisement on verso of last leaf.